Edukasi Pentingnya MP-ASI Sebagai Upaya Pencegahan Stunting Pada Masa Golden Anak - Indriyani, Okti; Putri, Noviyati Rahardjo (Universitas Sebelas Maret, 2023)
Mother's milk companion food (MP-ASI) is a complementary food to meet the nutritional needs of infants under five after six months of age. In practice there are still many Indonesian people giving MP-ASI at less than six months. This is what causes high incidence of infections such as diarrhea, airway infections, allergies to growth disorders. The high incidence of infection has an impact on the decline of the health of infants toddlers so that nutritional needs are not optimal that lead to stunting cases. Based on the results of basic health research in 2018, the prevalence of stunting in Indonesia is 30.8% and is still quite far from the WHO target of 20%. One of the causes of high stunting cases in Indonesia is the lack of mother's knowledge of her child's nutritional needs. Therefore, a promotive and preventive effort is needed by providing education the importance of giving MPASI, especially in the Golden Age period aged 6-24 months so that stunting problems are not a problem that always haunts children's health in Indonesia. It is hoped that this effort can significantly reduce stunting cases. The results of the preliminary study were obtained by most mothers who have toddlers in Pulosari Hamlet, Gayam, Sukoharjo lack understanding of the administration and processing of MPASI. The method carried out in this community service activity is in the form of giving counseling around MPASI followed by a discussion session to find out the level of mother's knowledge about the importance of giving MP-ASI in meeting the nutritional needs of her child. Participants in this community service as many as 30 mothers who have children aged 6 months-24 months and come to the posyandu Pulosari Hamlet, Gayam, Sukoharjo with nearly 90% of mothers do not understand the importance of MP-ASI but after being given education the mother's understanding can be seen in activeness Discuss and solve the problem of mothers in meeting the nutritional needs of children. carried out well and active participants discuss in these activities. In the future it is expected that community service can be carried out by practicing MPASI making.